2009
DOI: 10.1073/pnas.0903188106
|View full text |Cite
|
Sign up to set email alerts
|

7SK snRNP/P-TEFb couples transcription elongation with alternative splicing and is essential for vertebrate development

Abstract: Eukaryotic gene expression is commonly controlled at the level of RNA polymerase II (RNAPII) pausing subsequent to transcription initiation. Transcription elongation is stimulated by the positive transcription elongation factor b (P-TEFb) kinase, which is suppressed within the 7SK small nuclear ribonucleoprotein (7SK snRNP). However, the biogenesis and functional significance of 7SK snRNP remain poorly understood. Here, we report that LARP7, BCDIN3, and the noncoding 7SK small nuclear RNA (7SK) are vital for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
176
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(182 citation statements)
references
References 35 publications
5
176
0
Order By: Relevance
“…7SK snRNP and Brd4 control transcription elongation in different kinds of cells (Wu and Chiang 2007;Barboric et al 2009), but the phenotype of Larp7 mutant embryos revealed cell type-specific functions of 7SK snRNP in embryos. We investigated the expression of components of 7SK snRNP, Brd4, and IRF-1 in various embryonic tissues at E12.5.…”
Section: Ink4bmentioning
confidence: 99%
“…7SK snRNP and Brd4 control transcription elongation in different kinds of cells (Wu and Chiang 2007;Barboric et al 2009), but the phenotype of Larp7 mutant embryos revealed cell type-specific functions of 7SK snRNP in embryos. We investigated the expression of components of 7SK snRNP, Brd4, and IRF-1 in various embryonic tissues at E12.5.…”
Section: Ink4bmentioning
confidence: 99%
“…LARP7 has been shown to participate in the negative regulation of polymerase II transcribed genes through the 7SK RNP (Krueger et al 2008;Markert et al 2008;Barboric et al 2009;Diribarne and Bensaude 2009). LARP7 binds by means of its La motif onto the uridylic acid-rich 39 end of the 7SK RNA and allows the sequestration of the positive transcription factor pTEFb.…”
Section: Introductionmentioning
confidence: 99%
“…50 Another finding showed that the 7SK snRNP, which inhibits P-TEFb kinase activity, modulates not only transcription elongation but also alternative splicing. 51 Therefore, these observations infer that transcription elongation and alternative splicing are coupled, and that regulation of one process affects the rate of the other.…”
Section: Introductionmentioning
confidence: 99%